Computational intelligence algorithms for the development of an Artificial Sport Trainer - Fister, Iztok Jr. (Informatica, 2017)
<!--StartFragment-->This paper presents a short summary of doctoral thesis that proposes the use of computational intelligence algorithms for the development of an Artificial Sport Trainer.<!--EndFragment-->